Paediatric fractures of the tibia. Issue 5 (October 2018) - Pastides, Philip S.; Sun, Stephen Ng Man; Hulme, Alison; Evans, Stuart
Abstract: Fractures of the paediatric tibia are common and, as with all paediatric bone injuries, require specific attention based on the anatomical location and degree of displacement. It is paramount that the soft tissues are accurately assessed and managed appropriately. Lack of recognition of these injuries, or inappropriate management, may lead to long-term problems. This paper aims to review the mechanism of injury, management options and potential problems associated with these injuries.